PENGARUH INFLASI, SUKU BUNGA, LIKUIDITAS DAN LEVERAGE TERHADAP NILAI PERUSAHAAN - Cipta Sari, Ni Komang Sripeni; Wirawati, Ni Gusti Putu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.06.TAHUN.2024DO - 10.24843/EEB.2024.v13.i06.p08, 2024)
The investor's opinion of a company's success rate is reflected in its firm value. A high business value will lead the market to believe not just in the firm's current success, but also in its future potentialCompany values ??are very important. Because the higher the value of the company, the greater the wealth of the shareholders. This study purpose is to prove the effect of inflation, iinterest rates, liquidity, and leverage on firm value. The research of this study was conducted in Banking Companies listed on the Indonesia Stock Exchange for the period 2017-2021, with 16 sample companies using the purposive sampling method. Data collection was carried out using the documentation method by accessing the official website of the Indonesia Stock Exchange and the official website of each company. The data collected was then analyzed using multiple regression analysis. The study's findings reveal that inflation and interest rates have little influence on business value. Firm value is significantly influenced by liquidity. Leverage has a substantial negative impact on firm value. The implication of this research is that the information about inflation, iinterest rates, liquidity, and leverage can provide signals in making investment decisions to investors.